APPLICATION OF MULTIDIMENSIONAL SCALING ANALYSIS IN MAPPING PRODUCT PREFERENCES ATTRIBUTE (CASE STUDY: CUSTOMER KECAP BANGO AND ABC) - Dahua, Dwieshinta Juniati; Tumbuan, Willem J. F. A.; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: This research analyzed by using a multidimensional scaling analysis. To get accurate results from this method that became the goal of the study, researchers analyzed the atribuut perceptual mapping product soy sauce based on the 4 attributes; brand, price, labels and packaging. This study uses comparative quantitative approach, the population of this study are the people who buy and use soy sauce ABC and BANGO. The sample of this research is the 100 respondents with data obtained through questionnaires. The findings of this study indicate that the attribute labels have similarities between ABC and BANGO, but there were no significant effects for consumers because the location between quadrant is still far away and for a better recommendation for any manufacturer of soy sauce to pay more attention to product attributes that already exist in the product, soybean sauce because the product attribute has a huge effect on consumer preference.Keywords: product attribute, consumer preferences, multidimensional scaling